Tryptophan as a biomarker of pregnancy-related immune expression and modulation: an integrative review - Prescott, Stephanie; Billeci, Natasa; Gotcher, Melissa; Patel, Sapna; Almon, Addison; Morgan, Hailey; Abukhalaf, Danielle; Groer, Maureen (Frontiers in Reproductive Health, 2025)
BackgroundDegradation pathways of Tryptophan (TRP) are implicated in a spectrum of physiological adaptations and outcomes associated with pregnancy. The immunomodulatory role of TRP and its metabolites through the indoleamine 2,3-dioxygenase (IDO) pathway is particularly relevant to pregnancy due to its potential influence on maternal and fetal immune tolerance and the mother's health.MethodsA targeted literature search was conducted via PubMed, Web of Science, and Embase, focusing on maternal serum TRP levels in pregnancy. We included original human subject research on maternal serum TRP, published in English within the last five years. We included 16 quality studies with direct measurement of TRP in pregnancy including ten prospective cohorts, four case-control studies, and two cross-sectional studies.ResultsTRP levels are reduced both pre- and postnatally in women with depressive symptoms, but not during pregnancy, though the TRP/Kynurenine pathway is disturbed during pregnancy in women with depressive symptoms, women with prolonged labor, women with gestational hypertension, and in adverse outcomes of pregnancy including prematurity and growth restriction.ConclusionTRP and its metabolites hold promise as biomarkers for various pregnancy-related outcomes. Future research should aim to clarify the mechanisms by which TRP metabolism influences maternal and fetal health outcomes.